2013
DOI: 10.1159/000351353
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Impact of Cold Atmospheric Pressure Plasma on Medical Critical Yeasts and Bacteria Cultures

Abstract: Objectives: Plasma medicine focuses on the application of cold atmospheric pressure plasmas (CAPs) in or on the human body. So far, plasmas have been used to sterilize implant materials or other thermally unstable medical products and have been applied for chemical surface modifications. This study investigates the antimicrobial effect of physical plasmas on microorganisms which cause skin infections, such as Staphylococcus aureus, Pseudomonas aeruginosa and Candida albicans, depending on the plasma source and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 83 publications
(64 reference statements)
0
37
0
1
Order By: Relevance
“…Some of these studies showed differences in the susceptibility of MRSA and MSSA strains to plasma treatment for the planktonic form and after biofilm cultivation, with an increased survival rate of approximately 6% after treatment for 2 min [27], and from 5 up to 70% after treatment for 3 min on agar plates [24,25]. Other authors reported an increased susceptibility of 1 MRSA and 1 MSSA strain compared to 2 MRSA strains (USA300 and USA400) in planktonic conditions [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these studies showed differences in the susceptibility of MRSA and MSSA strains to plasma treatment for the planktonic form and after biofilm cultivation, with an increased survival rate of approximately 6% after treatment for 2 min [27], and from 5 up to 70% after treatment for 3 min on agar plates [24,25]. Other authors reported an increased susceptibility of 1 MRSA and 1 MSSA strain compared to 2 MRSA strains (USA300 and USA400) in planktonic conditions [29].…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial activity of the kINPen09® has been investigated against a wide spectrum of microorganisms [20,21,22,23,24], and has demonstrated the ability to reduce the number of microorganisms, such as methicillin-sensitive Staphylococcus aureus (MSSA) and methicillin-resistant S. aureus strains (MRSA, carrying the mecA gene) [25,26,27,28]. However, testing the efficacy of CAP on culture plates or biofilm showed varying effects, and details of the results pertaining to the application of plasma against S. aureus strains with or without the presence of the mecA gene indicate a possible increased tolerability of mecA + strains [25,27,29].…”
Section: Introductionmentioning
confidence: 99%
“…This plasma jet consists of a concentric inner electrode driven by a high-frequency power supply and a grounded outer electrode [17,18,19,20]. The plasma is ignited between both electrodes and flows out of an opened nozzle.…”
Section: Methodsmentioning
confidence: 99%
“…The studies showed that CAPs exhibit profound bactericidal and fungicidal properties in vitro depending on the chosen plasma parameters, in particular on the process gas used, the input power, and the number of treatments performed [17]. The aim of this paper is to investigate the interaction of CAP generated by the plasma MEF nozzle with human skin cells.…”
Section: Introductionmentioning
confidence: 99%
“…The microbicidal effect of CAP was observed in vitro [256,257,258,259,260,261] on skin and chronic wounds, and exceeds the effectiveness of CHD, PVP-I, and PHMB. In a 3D epidermis model, CAP displayed dose- and time-dependent compatibility [256]; P. aeruginosa was inactivated without destroying the structure of the epidermis.…”
Section: Future Perspectivesmentioning
confidence: 99%